Toxic Activity, Molecular Modeling and Docking Simulations of Bacillus thuringiensis Cry11 Toxin Variants Obtained via DNA Shuffling - Florez, Alvaro Mauricio; Suarez-Barrera, Miguel Orlando; Morales, Gloria M.; Rivera, Karen Viviana; Orduz, Sergio; Ochoa, Rodrigo; Guerra, Diego; Muskus, Carlos (Frontiers in Microbiology, 2018)
The Cry11 family belongs to a large group of -endotoxins that share three distinct structural domains. Among the dipteran-active toxins referred to as three-domain Cry11 toxins, the Cry11Aa protein from Bacillus thuringiensis subsp. israelensis (Bti) has been the most extensively studied. Despite the potential of Bti as an effective biological control agent, the understanding of Cry11 toxins remains incomplete. In this study, five Cry11 variants obtained via DNA shuffling displayed toxic activity against Aedes aegypti and Culex quinquefasciatus. Three of these Cry11 variants (8, 23 and 79) were characterized via 3D modeling and analysis of docking with ALP1. The relevant mutations in these variants, such as deletions, insertions and point mutations, are discussed in relation to their structural domains, toxic activities and toxin-receptor interactions. Importantly, deletion of the N-terminal segment in domain I was not associated with any change in toxic activity, and domain III exhibited higher sequence variability than domains I and II. Variant 8 exhibited up to 3.78- and 6.09-fold higher toxicity to A. aegypti than Cry11Bb and Cry11Aa, respectively. Importantly, variant 79 showed an -helix conformation at the C-terminus and formed crystals retaining toxic activity. These findings indicate that five Cry11 variants were preferentially reassembled from the cry11Aa gene during DNA shuffling. The mutations described in loop 2 and loop 3 of domain II provide valuable information regarding the activity of Cry11 toxins against A. aegypti and C. quinquefasciatus larvae and reveal new insights into the application of directed evolution strategies to study the genetic variability of specific domains in cry11 family genes.